Introducing care management to Brazil’s alcohol and substance use disorder population - Pinsky,Ilana (2018)
Brazil has a sizable alcohol and substance use disorder (ASUD) population, yet there are considerable gaps in treatment access and retention. ASUD, a chronic medical condition, is highly comorbid with medical and behavioral health disorders. This indicates a need for more targeted interventions in order to achieve health care integration (a major goal of Brazil’s health care system). Care management – that is, the organization of patient care by an institution – is a viable strategy to engage individuals with ASUD who might benefit from treatment but are not aware of or do not use the available resources, as well as to help maintain patients in treatment. Care management is considered an essential supplement to the treatment of chronic disease. The objective of this article is to discuss the applicability of care management for the treatment of ASUD within the public health care system in Brazil. We describe models of care management that have been adopted internationally and identify the feasibility and advantages for its adoption in Brazil.